EFFECT OF MOTIVATION AND TRAINING TO EMPLOYEES PERFORMANCE - Aris Setiawan Djody; Hari Susanta Nugraha; Sari Listyorini (Universitas Diponegoro, 2014)
Commonly, every company in running its operational activity requires supported factor that to achieve good performance and high productivity. Human resources is one of the most important factors, because in the absence of good quality of the role of quality human resources, company activities will not be implemented optimally. To achieve a company goals, employees need motivation to improve performance. In addition motivation factor of work, the need for training as a process that complement of workers to get knowledge with specialized skills. This study was conducted to determine the effect of training on motivation to performance of the production employees case studies on women workers in PT. Ungaran Sari Garment Unit Pringapus. In this study the data obtained using the technique of random sampling with sample determination that is done with the formula in the opinion of Slovin as many as 98 respondents. Analysis that conducted is multiple regression analysis, hypothesis testing via t-test and F-test, the coefficient of determination and cross-tabulations. From the analysis of regression the equation result is Y = 6.040 + 0,097X1+ 0,275X2. Where the performance variable (Y), motivation (X1), and training (X2). Hypothesis testing using t test and F test showed that the two independent veriabel studied was shown to significantly affect the performance dependent variable. Suggestion that proposed by author, among others, should emphasize the importance of regulating others, reach a future in the company, seeking feedback in the work and the opportunity to achieve the goals (ideals) life / work. Moreover, the authors also suggested to maintain the achievements of training that already good and reduce the error rate in the work by analyzing mistakes that often in job then provide specific training to employees about the mistakes often made when the employee works.